If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + 2) = 54 Reorder the terms: 9(2 + x) = 54 (2 * 9 + x * 9) = 54 (18 + 9x) = 54 Solving 18 + 9x = 54 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 9x = 54 + -18 Combine like terms: 18 + -18 = 0 0 + 9x = 54 + -18 9x = 54 + -18 Combine like terms: 54 + -18 = 36 9x = 36 Divide each side by '9'. x = 4 Simplifying x = 4
| 3x+8+4x=-8(x-6)-8(13+5) | | 5b+5c= | | (z/5)=(3/10)z+7 | | 2+10x=4x+20 | | 13x+1=83x+4 | | x^2+34x+45=0 | | -9x-1=-46 | | y/3-6=-9 | | -3(2m+1)+7=-5 | | 3v-3=24 | | (-2/3)x=-2 | | 20a^3-15a^2+125=0 | | (1/4)x=-2 | | y=-4(x-3)squared-3 | | 4(2-x)-2=5-4x | | x+12=-11 | | 5r+54=169 | | x+y=84 | | -10x-2=-12 | | y=-4(x-3)2-3 | | 5/47x+25/47+15/47 | | -(4xy-12)+2(6xy+5)= | | 115=7f-18 | | 9r-23=-17+6r | | 2(5v)= | | -4+17=1 | | 4x-25=-1+6x | | 125x^2-167x+36=0 | | 2x-36=5x | | 3x+15=-12 | | 3g+3(2-g)+4(g+1)= | | 6-(-5r)=10r-6 |